Atividade do interferon tipo I suíno na proteção contra o vírus da febre aftosa (FMDV) - Botton, Sônia de Avila (2005)
The objective of this study is to evaluate the adjuvant effect of interferon alpha (IFNα) in swine vaccinated with a recombinant replication-defective adenovirus containing foot-and-mouth disease virus (FMDV) protein coding regions, as well as to understand the molecular mechanisms involved in the interaction of FMDV with its host. In the first part of this thesis, the adjuvant effect of pIFNα was evaluated in swine vaccinated with a recombinant vaccine delivered by a human adenovirus type 5 (Ad5) vector containing FMDV capsid (P1-2A) and 3Cpro proteinase coding regions (Ad5-A24). Swine were separated into 5 groups and inoculated with low (5x108 PFU) or high (5x109 PFU) doses of Ad5-A24 in the presence or absence of pIFNα (Ad5-pIFN, 109 PFU). Control animals received 6x109 PFU of an Ad5 vector containing the glycoprotein gene of vesicular stomatitis virus (Ad5-VSNJV-G). All swine were challenged at 42 days post vaccination (dpv) with FMDV-A24. Prior to challenge, blood samples were examined for IFN production, induction of IFN-induced genes (ISG s), FMDV-specific neutralizing antibodies and FMDV-specific antibody isotypes. After challenge, a number of parameters were analyzed including clinical score, viremia, lymphopenia and antibodies against FMDV structural (S) and non-structural (NS) proteins. The results indicate that both groups that received high-dose Ad5-A24 developed an FMDV-specific neutralizing antibody response by 14-21 dpv, which was maintained until the day of challenge. Both high-dose groups developed high levels of IgG1 and IgG2, however the IgG1 response was higher. The high-dose Ad5-A24 with IFN group developed higher levels of IgG1 than the group administered only high-dose Ad5-A24 and this difference was statistically significant. Antiviral activity and IFNα were detected in the groups that received IFN. The three ISG s examined, PKR, OAS and Mx1, were detected by real time RT-PCR in leukocytes from Ad5-pIFNα-vaccinated swine. After challenge, all animals in the control group developed early viremia, vesicular lesions, considerable lymphopenia and antibodies to FMDV NS proteins. The animals that received low-dose Ad5-A24 without IFN had similar clinical signs, except that fewer animals had viremia. In contrast, pigs inoculated with the low-dose Ad5-A24 and IFNα had a delayed onset of vesicular lesions and only one animal had detectable viremia. Animals vaccinated with high-dose Ad5-A24 without IFNα had no viremia, showed fewer lesions, one animal had no lesions, and delayed onset of disease compared to the low-dose Ad5-A24 groups. Four of five pigs vaccinated with high-dose Ad5-A24 and IFNα were completely protected from disease and only one animal in this group had a vesicular lesion restricted to the site of challenge virus inoculation. The results indicate that IFNα enhances the level of protection induced by the Ad5-FMD vaccine against homologous FMDV, supporting the use of IFNα as a potential adjuvant in FMD vaccination strategies. To investigate the effect of FMDV infection on the induction of the host IFN-α/β response, swine cells were infected with wild-type (WT) FMDV and a mutant FMDV lacking the L proteinase (Lpro) coding region (A12-LLV) at different multiplicities of infection. The synthesis of IFN-α and IFN-β mRNAs and three well characterized ISG s, PKR, OAS, and Mx1 mRNA, were evaluated by real time RT-PCR. A12-LLV infection resulted in significantly higher levels of induction of IFN-β mRNA as compared to WT virus infected cells, while IFN-α mRNA was not induced after either infection. The increased levels of IFN-β mRNA in A12-LLV-infected cells correlated with higher levels of induction of PKR, OAS and Mx1 mRNAs and antiviral activity. By using RNA interference (RNAi) technology to knock-down PKR mRNA expression, it was possible to demonstrate that the yield of A12-LLV was increased up to 200-fold, supporting the role of PKR as an inhibitor of FMDV replication. These results confirm that Lpro down regulates the innate immune response to FMDV infection at multiple levels. Previous studies indicated that control was at the translation initiation level by Lpro cleavage of translation initiation factor eIF-4G. The present data demonstrates that regulation also occurs at the level of transcription by inhibition of IFN-β mRNA induction through an unknown mechanism.